Community Participation in Cultural Preservation in Gerendeng Pulo Village, Karawaci District, Tangerang City - Pratala, Esaka; Sugara, Asep; Supriadi, Yudi Nur (Garuda Prestasi Nusantara Consulting, 2024)
This research aims to describe community participation in cultural preservation in Gerendeng Pulo Village. Based on the research results, information was obtained that there is a form of community participation in Gerendeng Pulo Village to preserve Chinese ethnic culture, namely the participation of workers in mutual cooperation to improve a clean, neat and green environment with the concept of Chinese cultural values ​​to eliminate the stigma of slum villages becoming cultural villages, participation property, namely donations of money and goods which are managed by the community and then used for cultural preservation purposes. Participation in constructive ideas such as the idea of ​​thematic improvement of Gerendeng Pulo village and providing the concept of cultural preservation through the implementation of Cap Go Meh activities as a promotion to introduce Gerendeng Village. Pulo, Participation takes the form of ability or expertise that is used to encourage, mobilize and motivate the people of Kampung Gerendeng Pulo to be actively involved in improving the environment and preserving culture. The Tangerang City Government needs to be responsible for supporting the development and preservation of culture in Gerendeng Pulo Village from various aspects, to provide stimulus and not provide excessive intervention.